Vigilancia activa de infecciones asociadas a la atención en salud en unidades de cuidado intensivo: perfil de resistencia y molecular en un país en desarrollo - Margarita Maria Ochoa-Diaz (Asociación Colombiana de Infectología, 2022)
Objective: This study aimed to characterize epidemiological and molecular profile of Healthcare-associated infections [HAI] in 21 intensive care units (ICU) in a city in Colombia.Methods:Descriptive study of prevalence. Adult patients were screened in 21 ICUs for HAIs: VAP, CLABSI; CAUTI and/or SSI. Microbiological and genotypic iden-tification was performed.Results: Prevalence of HAIs was 41.4% (CI 36.9-45.9).VAP 15.8% (CI 12.7-19.4); CLABSI, 13.5% (CI 10.6-16.9); CAUTI, 7.7% (CI 5.5-10.5); and SSI, 4.4% (CI 2.7-6.6). Gram-negative bacteria (71.7%) predominated (P. aeruginosa (19.1%), K. pneumoniae (13.4%) and E. coli (13%)). Pseudomonas spp. 20-30% were resistant to car-bapenems and ≥ 10% to aztreonam, 3rd- and 4th-generation cephalosporins, and β-lactamase inhibitors. In VAP and CLABSI, 30% of Staphylococcus aureus were resistant to oxacillin. In CAUTI, Staphylococcus epidermidis exhibited 100% resistance. In P. aeruginosa resistance gene were blaTEM, blaSHV, and blaCTX-M (15-32%), KPC (5.7%), and oxacillinases blaOXA-48 (1.8%) and blaOXA-1-40-30 (20-50%). In E. coli, genes qnrB, qnrS and qnrD were identified. In CLABSI, ermC-type (16.7%), aph[2']'If (7.7%) and ant[4']-Ia (7.7%) were identified in Staphylococcus aureus. Conclusions: VAP and CLABSI predominate in ICUs evaluated in Colombia due to resistant gram-negative bacteria by ESBL-type resistance genes plasmids, efflux pumps hindering the therapeutic approach.